Optimizing the hydroxyapatite nanocrystals derived from biological sources to increasing efficiency and quality - Mahsa Abbasi; Hossein Derakhshankhah; Soheila Kashanian; Zhila Izadi; Mohammad Soleiman Beigi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Hydroxyapatite is one of the most essential bioactive and biocompatible ceramics. Due to its unique properties and its structural similarity to bone, it has many applications in medicine, dentistry, and bone tissue engineering. Therefore, many methods and strategies have been studied to prepare hydroxyapatite. The purpose of this study was to optimize hydroxyapatite nanocrystals prepared from biological sources with higher efficiency and quality. Materials & Methods: This study synthesized and analyzed hydroxyapatite from White Sea shells using simple and affordable methods like ultrasonic, hydrothermal, and thermal-ultrasonic decomposition. White seashells contain carbonate-calcium (CaCO3). For the synthesis of hydroxyapatite, environmentally friendly solvents such as water (green synthesis) and di ammonium hydrogen phosphate (ADP) were used as a source of phosphate. The data were analyzed using Graph Pad Prism V.10 statistical software, and the level of significance was considered less than 0.05. Results: Hydroxyapatite was synthesized by the ultrasonic method and was chosen as the most appropriate. Because in the EDX results, the percentage of elements oxygen and phosphorus (O, P) in the hydroxyapatite synthesized by the ultrasonic method corresponds to the data of the standard card, HA~1.67, and for this reason, the ultrasonic method is better than the other two methods (hydrothermal and thermal-ultrasonic decomposition) and is more suitable. In FTIR, phosphate, hydroxide, and carbonate (PO43-), OH, and CO32- groups were observed, which indicate the synthesis of hydroxyapatite. With SEM and FE-SEM, the morphology and size of hydroxyapatite particles were observed to be between 16.5 and 70.80 nm. XRD analysis, crystallinity, and needle-like structure of hydroxyapatite were observed. The blood compatibility results showed that hydroxyapatite had no significant hemolysis. Examining the cell compatibility of hydroxyapatite on bone-like cells (MG63) showed a survival rate of over 90%, and cell proliferation was statistically (Graph Pad Prism 10) significant (P < 0.05). Conclusion: One of the most effective methods for preparing hydroxyapatite involves conducting the reactions at the bottom; the ultrasonic method's affordability and cost-effectiveness are among its positive features, as it can generate multiple processes throughout the production process. The results demonstrated that this method produced a material with a hexagonal structure, nanometer size, and suitable biocompatibility.